Marketing of Library and Information Services Through Website: a Case Study on the Official Website of Tengku Anis Library, UITM Kelantan Branch, Malaysia - Faisal Fahmi,; Nila Arofa’ina, (Literatify : Trends in Library Developments, 2023)
The purpose of writing this article is to find out how the implementation of library marketing and information services carried out by the Tengku Anis Library UiTM Kelantan. The method used is a literature study of scientific articles relevant to the topic and observation on the Tengku Anis Library website. The results show that library marketing activities and information services are carried out by Tengku Anis Library. One of the media is the official website as a form of their adaptation to technological developments. In conducting information marketing activities, the process starts from analyzing market opportunities, selecting target markets, developing a marketing mix, and developing marketing strategies and managing marketing programs. They have implemented these four steps so that the marketing process until the product reaches the library users can take place well. However, there is one thing that is still lacking in the process, which is the relatively lacking aspect of market segmentation. The author recommends conducting more specific market segmentation activities so that the intended market is more appropriate so that the product can be used evenly.